First Reports of Macrosaccus morrisella (Lepidoptera: Gracillariidae) Feeding on Soybean, Glycine max (Fabales: Fabaceae). Issue 1 (24th November 2021) - Koch, Robert L; Moisan-De Serres, Joseph; Ribeiro, Arthur V
Abstract: Macrosaccus morrisella (Fitch) is a tiny leaf-mining moth native to North America. In this publication, we provide first reports of this insect feeding on soybean, Glycine max (L.) Merr., in Canada and the United States, describe its injury to soybean, and briefly review leaf miners associated with soybean. Further efforts related to M. morrisella should focus on its geographic extent of infestation of soybean, impacts to soybean, and ecology in the agricultural landscape.